Multiple loci with different cancer specificities within the 8q24 gene desert - Ghoussaini, Maya; Song, Honglin; Koessler, Thibaud; Al Olama, Ali Amin; Kote-Jarai, Zsofia; Driver, Kristy E; Pooley, Karen A; Ramus, Susan J; Kjaer, Susanne Krüger; Hogdall, Estrid; DiCioccio, Richard A; Whittemore, Alice S; et al. (JNCI : Journal of the National Cancer Institute, 2008)
Recent studies based on genome-wide association, linkage, and admixture scan analysis have reported associations of various genetic variants in 8q24 with susceptibility to breast, prostate, and colorectal cancer. This locus lies within a 1.18-Mb region that contains no known genes but is bounded at its centromeric end by FAM84B and at its telomeric end by c-MYC, two candidate cancer susceptibility genes. To investigate the associations of specific loci within 8q24 with specific cancers, we genotyped the nine previously reported cancer-associated single-nucleotide polymorphisms across the region in four case-control sets of prostate (1854 case subjects and 1894 control subjects), breast (2270 case subjects and 2280 control subjects), colorectal (2299 case subjects and 2284 control subjects), and ovarian (1975 case subjects and 3411 control subjects) cancer. Five different haplotype blocks within this gene desert were specifically associated with risks of different cancers. One block was solely associated with risk of breast cancer, three others were associated solely with the risk of prostate cancer, and a fifth was associated with the risk of prostate, colorectal, and ovarian cancer, but not breast cancer. We conclude that there are at least five separate functional variants in this region.